Case Study of Nurses' Experiences Related to the Deaths of Their Patients. Issue 4 (October 2018) - Mast, Miriam; Gillum, Deborah
Abstract : A qualitative case study methodology was applied to explore how nurses cope when their patients die. The study utilized a sample of 16 participants at a rural 123-bed community hospital. Nine themes regarding nurses dealing with grief emerged: ( a ) family issues, ( b ) patient alone at death, ( c ) knowing the community, ( d ) never-forgotten experiences, ( e ) first experiences, ( f ) time issues, ( g ) responses to unexpected deaths, ( h ) role of nurses, and ( i ) nurses' response to death itself. It is concluded that nurses need to grieve. If nurses do not know how to cope with deaths of their patients, it may lead to personal health issues. There is a need for further research to evaluate whether improved end-of-life education and counseling address the needs of the nurses who deal with deaths of their patients. Globally, nurses cope with death and need to grieve when their patients die. Knowledge introduced from this research adds to the knowledge of the skills and coping of nurses everywhere.